(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay reflects on Guido Davide Neri’s philosophical existence entirely spent according to the precepts of a phenomenology of life due to his ability to mix concretely with the historical facts from which he moved his theoretical path. A path that has been always hooked to the world of life. Under the influence of Merleau-Ponty’s thinking, which renews Husserl’s pure consciousness through the embodied subjectivity, Neri’s thought became gradually more and more historical, getting in touch with places where history was maximally alive, the early 1960’s. In Prague Guido looks for socialism and, through his living in the world, he is among the first to deal with the philosophical issue of an European identity chance.